OILA VA UNING DEMOGRAFIK TARAQQIYOTI - Xudoyorov, L.X.; Jabborova, M.H. (SCIENCE and SOCIETY, 2024)
In this article, the concept of family and its object of study were presented by local and foreign scientists, as well as the basis of the family, according to the definition of the UN, "A family is the unity of all human families", it is a small link of society, described that the homeland is the homeland within. The analysis of the results of the social survey on the topic "How many children is better in a family" together with the scientific and practical center of Kashkadarya region "Family" was also presented.
Keywords: society; child; socio-economic development; food; clothing; housing; demographic criterion; social criterion; economic criterion